2021
DOI: 10.1016/j.ijhydene.2020.09.078
|View full text |Cite
|
Sign up to set email alerts
|

On the CFD modelling of hydrogen dispersion at low-Reynolds number release in closed facility

Abstract: Hydrogen release inside closed facilities could cause explosions with harmful consequences. Safety assessment should be performed in order to design prevention and mitigation measures in case of such an accident. A numerical study for helium (as hydrogen surrogate) accumulation inside a closed facility representative of a real-scale garage at low release rate is conducted. Due to the nature of the examined flow several turbulence modelling approaches (RANS and LES type) and the laminar approach were examined w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The Favre-averaged Navier-Stokes equations with the Boussinesq assumption for the Reynolds stresses are solved, along with the equation for the hydrogen mass fraction (Einstein summation notation is used): The simulations were performed using the ADREA-HF CFD code, which has been extensively validated in the past for hydrogen dispersion applications, including cases of confined and semi-confined geometries [36][37][38][39][40]. The Unsteady Reynolds-Averaged Navier-Stokes (URANS) methodology was used with the finite-volume method on a staggered Cartesian grid.…”
Section: Methodsmentioning
confidence: 99%
“…The Favre-averaged Navier-Stokes equations with the Boussinesq assumption for the Reynolds stresses are solved, along with the equation for the hydrogen mass fraction (Einstein summation notation is used): The simulations were performed using the ADREA-HF CFD code, which has been extensively validated in the past for hydrogen dispersion applications, including cases of confined and semi-confined geometries [36][37][38][39][40]. The Unsteady Reynolds-Averaged Navier-Stokes (URANS) methodology was used with the finite-volume method on a staggered Cartesian grid.…”
Section: Methodsmentioning
confidence: 99%
“…When the wind speed exceeded 1.5 m/s, the decrease in the volume of combustibles was not significant, indicating that forced convection environment can change the combustible volume produced by hydrogen leakage. Previous studies have found that ambient wind has a vital influence on hydrogen diffusion, but its research scenes mainly focus on semi-ventilated environments [14] or enclosed spaces [15,16] such as hydrogen refueling stations [17,18] and parking lots [19,20]; the influence of longitudinal wind on hydrogen leakage during the driving of FCVs has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Also, Liang et al [21] studied the effect of wind speeds and directions on the ventilation rates of a semi-opened room. With the presence of this large number of experiments, many benchmark simulations, like the work of Venetsanos et al [22] and Giannissi et al [23], have been carried out, to validate the different CFD tools in hydrogen leakage simulations.…”
Section: Introductionmentioning
confidence: 99%